BTPN Syariah Customer Assistance Strategy in the Syariah Mobile Marketing Area of Pengasih District - Permatasari, Siviana; Oktafia, Renny; Nisa, Fauzatul Laily (Unram Journal of Community Service, 2025)
The mentoring program for BTPN Syariah customers through the Mobile Marketing Syariah approach in Pengasih District aims to enhance the economic capacity of productive underprivileged communities. This program adopts the Asset-Based Community Development (ABCD) method, focusing on identifying and leveraging community assets to promote Sharia-based economic empowerment. The results demonstrate improvements in financial management skills, including the ability to separate business and personal finances. Additionally, there is an increase in customers’ confidence, accompanied by the adoption of simple technologies such as digital financial recording applications and e-commerce platforms. In the marketing aspect, customers successfully expanded their market reach to broader levels. The program also fostered the creation of sustainable community support systems, such as profit-sharing schemes within business groups. However, challenges such as limited infrastructure and technology access remain and require collaborative solutions. Continued mentoring and capacity building for facilitators are expected to strengthen the positive impact of this program, supporting holistic and sustainable empowerment of underprivileged communities